2013
DOI: 10.1371/journal.pone.0066182
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibroblast Growth Factor 23 Concentration Is Increased and Predicts Mortality in Patients on the Liver-Transplant Waiting List

Abstract: High plasma fibroblast growth factor-23 (FGF23) concentration predicts the risk of death and poor outcomes in patients with chronic kidney disease or chronic heart failure. We checked if FGF23 concentration could be modified in patients with end stage liver disease (ESLD) and predict mortality. We measured plasma FGF23 in 200 patients with ESLD registered on a liver transplant waiting list between January 2005 and October 2008. We found that median plasma FGF23 concentration was above normal values in 63% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 60 publications
1
49
1
Order By: Relevance
“…According to the present observations, the high FGF23 plasma concentration in heart failure [10,11], acute renal failure [12], chronic kidney disease [11,13,14], diabetic nephropathy [15] and hepatic failure [16] could at least in part be secondary to the hyperaldosteronism associated with these diseases. The effect of aldosterone may at least partially be mediated by the serum & glucocorticoid inducible kinase SGK1, which is up-regulated by aldosterone and during diabetes [36] and is known to up-regulate Orai1 [23].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…According to the present observations, the high FGF23 plasma concentration in heart failure [10,11], acute renal failure [12], chronic kidney disease [11,13,14], diabetic nephropathy [15] and hepatic failure [16] could at least in part be secondary to the hyperaldosteronism associated with these diseases. The effect of aldosterone may at least partially be mediated by the serum & glucocorticoid inducible kinase SGK1, which is up-regulated by aldosterone and during diabetes [36] and is known to up-regulate Orai1 [23].…”
Section: Discussionmentioning
confidence: 54%
“…Excessive plasma FGF23 levels are observed and are associated with accelerated disease progression, morbidity and/or mortality in several clinical disorders including cardiac failure [10,11], acute renal failure [12], chronic kidney disease [11,13,14], diabetic nephropathy [15] and hepatic failure [16]. The pathophysiological significance of enhanced FGF23 formation, has, however, remained ill-defined [17,18] and little is known about mechanisms accounting for the up-regulation of FGF23 release in these clinical disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with cardiac failure [16,17], acute renal failure [18], chronic kidney disease [7,17,19], diabetic nephropathy [20] and hepatic failure [21], plasma FGF23 concentrations are high and associated with accelerated disease progression, morbidity and/or mortality. Mechanisms up-regulating FGF23 in those disorders are still ill-defined.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, high FGF-23 levels were not explained by decreased renal function. They also found in an experimental model that the damaged liver of diethyl-nitrosamine-treated mice expressed FGF-23 mRNA whereas healthy livers of control mice did not [40]. Additionally, in a more recent study by Wasserman et al high FGF-23 levels were described in 2 infants with liver disease due to biliary atresia who had developed a form of hypophosphatemic rickets.…”
Section: Fgf-23 and Alcoholic Liver Diseasementioning
confidence: 93%
“…Nafi di et al, (2009) reported that partial hepatectomy led to increased FGF-23 levels [38], and later, Raimann et al, (2013) showed that liver tissue could express mRNA for FGF-23 [39]. In the same year Prie et al found that high FGF-23 levels predict the risk of death in patients with end stage liver disease on a liver transplant waiting list [40]. In these patients, high FGF-23 levels were not explained by decreased renal function.…”
Section: Fgf-23 and Alcoholic Liver Diseasementioning
confidence: 99%